Improving oral health and related health behaviours (substance use, smoking, diet) in people with severe and multiple disadvantage: a systematic review of effectiveness and cost-effectiveness of interventions - McGowan, Laura J.; John, Deepti A.; Kenny, Ryan P. W.; Joyes, Emma C.; Adams, Emma A.; Shabaninejad, Hosein; Richmond, Catherine; Beyer, Fiona R.; Landes, David; Watt, Richard G.; Sniehotta, Falko F.; Paisi, Martha; et al. (PLOS ONE, 2024)
Background People experiencing homelessness co-occurring with substance use or offending (‘severe and multiple disadvantage’ SMD) often have high levels of poor oral health and related health behaviours (particularly, substance use, smoking, poor diet). This systematic review aimed to assess the effectiveness and cost-effectiveness of interventions in adults experiencing SMD to improve oral health and related health behaviours. Methods and findings From inception to February 2023, five bibliographic databases (MEDLINE, EMBASE, PsycINFO, CINAHL, and Scopus) and grey literature were searched. Two researchers independently screened the search results. Randomized controlled trials (RCTs), comparative studies and economic evaluations were included that reported outcomes on oral health and the related health behaviours. Risk of bias was assessed and results narratively synthesized. Meta-analyses were performed where appropriate. This review was registered with PROSPERO (reg. no: CRD42020202416). Thirty-eight studies were included (published between 1991 and 2023) with 34 studies reporting about effectiveness. Most studies reported on substance use (n = 30). Interventions with a combination of housing support with substance use and mental health support such as contingent work therapy appeared to show some reduction in substance use in SMD groups. However, meta-analyses showed no statistically significant results. Most studies had short periods of follow-up and high attrition rates. Only one study reported on oral health; none reported on diet. Three RCTs reported on smoking, of which one comprising nicotine replacement with contingency management showed improved smoking abstinence at 4 weeks compared to control. Five studies with economic evaluations provided some evidence that interventions such as Housing First and enhanced support could be cost-effective in reducing substance use. Conclusion This review found that services such as housing combined with other healthcare services could be effective in improving health behaviours, particularly substance use, among SMD groups. Gaps in evidence also remain on oral health improvement, smoking, and diet. High quality studies on effectiveness with adequate power and retention are needed to address these significant health challenges in SMD populations.
Gesehen am 15.01.2025